PEMETAAN HOTEL UNTUK MENUNJANG POTENSI WISATA DI DAERAH ISTIMEWA YOGYAKARTA BERBASIS MOBILE - Deny Ardyrusmarryya; Erna Kumalasari Nurnawati; Muhammad Sholeh (Jurnal Jarkom, 2016)
Special Region of Yogyakarta a top of major tourist after Bali Province. Yogyakarta have many special of tourism place. For support the tourism place, then many of hotel industrial to promote and give many information about our hotel. For that, have one mobile information system about hotel location in Special Region of Yogyakarta can to display into the map. Mobile operating system like Android currently very popular among mobile phone users, because almost everyone already have.The process of making this hotel Mapping System requires primary data and secondary data obtained from Government Tourism Office Special Region of Yogyakarta. This hotel mapping system uses location-based service that combines the process of mobile services with the geographical position of its. The mobile information system making use PHP, HTML, CSS, Java programming language, MySQL database, Apache web server, and Sublime Text Editor and Android Studio IDE. This system use UML modeling system, UML modeling use is Use Case Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. Results of this research is this system can helping user to give very detailed information about hotel location, ease to search hotel location and choose hotel categories, make it easy for users to open website and call hotel by one button, and ease to input coordinate location of hotel by operator.